دراسة تأثير عامل مقاومة الانزلاق على سلامة حركة العربات على الطرق المركزية في محافظة اللاذقية - أسعد شذى; محفوض علاء (Latakia University Journal -Engineering Sciences Series, 2019)
Traffic accidents are a serious negative phenomenon associated with different transport systems. Despite the relative recency of traffic accidents in societies, the inevitabile negative consequences of this phenomenon has led to intensifying efforts to study them in order to reduce their risks or to reduce their development. This study is an important step to study the effect of Skid-resistance factor on traffic accidents on central roads in Lattakia city in the absence of this measurement. This study was based on statistical method which examines the correlation between Skid-resistance and the number of fatalities, serious injuries and physical damage, which showed that the greatest effect of resistance to slip on the number of death Fuzzylogic was used to model traffic accidents and compare them with actual accidents. A Spatial analysis of traffic accidents on the road of "Alsahel.Alghab" was carried out by using GIS program to determine the intensity of accidents on the mentioned road ,Thus determining the most dangerous locations on this road. تعد الحوادث المرورية ظاهرة سلبية خطيرة تترافق مع نظم النقل المختلفة, وتتميز بكثير من العوامل المؤدية لوقوعها, وبرغم الحداثة النسبية لظاهرة حوادث المرور في المجتمعات فإن حتمية النتائج السلبية لهذه الظاهرة قد أدت إلى تكثيف الجهود لدراستها بهدف تخفيف مخاطرها, أو للتقليل من تطورها. تشكل هذه الدراسة خطوة مهمة لدراسة تأثير عامل مقاومة الانزلاق على الحوادث المرورية على الطرق المركزية في محافظة اللاذقية في ظل غياب كامل لهذا القياس. تم الاعتماد في هذه الدراسة على الطريقة الإحصائية التي درست الارتباط ما بين مقاومة الانزلاق و ما بين كل من عدد الحوادث, وعدد الوفيات والإصابات الجسيمة والأضرار المادية, والتي أظهرت أن أكبر تأثير لمقاومة الانزلاق كان على عدد الوفيات. كما تم استخدام المنطق الضبابي لنمذجة الحوادث المرورية ومقارنتها مع الحوادث الحقيقية. وتم إجراء تحليل مكاني للحوادث المرورية على طريق الساحل الغاب باستخدام برنامج GIS لتحديد كثافة الحوادث على الطريق المذكور, وبالتالي تحديد أكثر المواقع خطورة على هذا الطريق.